Distinct contributions of human hippocampal theta to spatial cognition and anxiety - Cornwell, Brian R. (2012)
Current views of the hippocampus assign this structure, and its prominent theta rhythms, a key role in both cognition and affect. We studied this duality of function in humans, where no direct evidence exists. Whole-head magnetoencephalographic (MEG) data were recorded to measure theta activity while healthy participants (N = 25) navigated two virtual Morris water mazes, one in which they risked receiving aversive shocks without warning to induce anxiety and one in which they were safe from shocks. Results showed that threat of shock elevated anxiety level and enhanced navigation performance compared to the safe condition. MEG source analyses revealed that improved navigation performance during threat was preferentially associated with increased left septal (posterior) hippocampal theta (specifically 4–8 Hz activity), replicating previous research that emphasizes a predominant role of the septal third of the hippocampus in spatial cognition. Moreover, increased self-reported anxiety during threat was preferentially associated with increased left temporal (anterior) hippocampal theta (specifically 2–6 Hz activity), consistent with this region’s involvement in mediating conditioned and innate fear. Supporting contemporary theory, these findings highlight simultaneous involvement of the human hippocampus in spatial cognition and anxiety, and clarify their distinct correlates.